Biogeochemical markers in juvenile Leach's storm-petrels (Hydrobates leucorhous) stranded offshore are distinct from inshore stranded juveniles and nestlings - Anne N.M.A. Ausems; Sophie Roy; Alexander L. Bond; Laura Crick; Joshua T. Cunningham; April Hedd; Laura A. McFarlane Tranquilla; Jennifer C. Rock; Robert A. Ronconi; Katharine R. Studholme; Christopher R.E. Ward; Sabina I. Wilhelm; et al. (Marine Pollution Bulletin, 2026)

Effects of pre-spawning heat stress on the fecundity of Acropora aspera - Morane Le Nohaic; Christopher Doropoulos; Selina Ward; Peter J. Mumby (Coral Reefs, 2026)
Repeated bleaching events driven by heat stress have caused extensive coral mortality and declines in survivors’ reproductive output, undermining reef recovery. On the Great Barrier Reef, heat stress events currently coincide with early oogenesis in many abundant taxa; with climate change, earlier onsets are expected to increasingly overlap later gametogenic stages. How coral reproduction responds as gametes mature in warmer waters remains unclear. To address this, we quantified the effects of heat stress during late gametogenesis on the fecundity of Acropora aspera . Using an ex situ experiment, gravid colonies were exposed to nine treatments combining three temperatures (Control + 1, + 2 °C) and three durations (3, 6, 9 weeks). Gravid polyp probability, polyp egg counts, egg volume, and testis volume were assessed at spawning. Responses were trait- and duration-specific. Sperm production was most sensitive, with testis volume declining ~ threefold under + 2 °C for 9 weeks relative to controls (0.056 mm 3 vs 0.160 mm 3 ); the same exposure nearly halved gravid polyp probability (0.015 vs 0.026 in Controls). However, 6-week exposure at + 2 °C increased sperm production (0.174 mm 3 ), highlighting the influence of exposure duration. In contrast, longer exposure to heat stress increased egg volume, which nearly doubled at + 1 °C (0.176 mm 3 vs 0.098 mm 3 in Controls); while egg counts remained stable, suggesting a strategy favouring better provisioned rather than numerous eggs. Nevertheless, larger gamete volumes may reflect stress-induced physiological changes rather than improved quality. These findings demonstrate that heat intensity, duration, and timing jointly shape coral reproductive investment, highlighting the complexity of predicting future reef recovery under climate change.

Urinary biomarkers of PAHs, VOCs, OPEs, and metal(loid)s in firefighters responding in the wildland urban interface (WUI) - Miriam M. Calkins; Alexander C. Mayer; Derek J. Urwin; Steve Bertke; Christine Toennis; Shawn C. Beitel; Jeff Hughes; Jamie Gabriel; Antonia M. Calafat; Christopher M. Reese; Julianne Cook Botelho; Maria Ospina; et al. (International Journal of Hygiene and Environmental Health, 2026)

Using Eye Lens Stable Isotopes to Identify the Rearing Origin of Fall Age‐0 Walleye ( Sander vitreus ) - Justin M. Sturtz; Benjamin J. Schall; Matthew J. Ward; Cody E. Treft; Steven R. Chipps; Christopher A. Cheek (Fisheries Management and Ecology, 2026)
Isotope values in fish eye lenses may be useful in differentiating rearing origins. We compared eye lens isotopic values of fall fingerling age‐0 walleye ( Sander vitreus ) reared in a hatchery pond, a recirculating aquaculture system (RAS), and a natural lake. Using 10 fish per rearing source, we delaminated layers from one eye lens per fish to assess temporal changes in carbon (δ 13 C) and nitrogen (δ 15 N) and pulverized the whole second eye lens for δ 13 C, δ 15 N, and sulfur (δ 34 S). RAS‐reared walleye values exhibited high precision among individuals and were δ 34 S enriched. Pond‐reared walleye had lower δ 13 C and δ 15 N core values compared to other rearing sources. For δ 13 C and δ 15 N, values remained consistent among layers for RAS‐reared walleye, δ 15 N slightly increased for pond‐reared and lake‐reared walleye, and δ 13 C increased substantially among subsequent layers in pond‐reared walleye. Bayesian 95% ellipses did not overlap among rearing sources. These results demonstrate that eye lens stable isotope analysis may be a useful tool for differentiating hatchery‐reared and wild large fingerling walleye, specifically from RAS‐ and pond‐reared sources.

Twelve distinct laboratory methods used to measure SARS-CoV-2 in wastewaters throughout a three-year Ontario-wide, Canada study: Impact on public health interpretation of disease incidence - Nada Hegazy; K. Ken Peng; Johanna de Haan-Ward; Elizabeth Renouf; Elizabeth Mercier; Shen Wan; X. Joan Hu; Charmaine Dean; Mark Servos; Elizabeth Edwards; Gustavo Ybazeta; Marc Habash; et al. (Journal of Water Process Engineering, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Building climate resilient urban forests: Impacts of irrigation and heat on tree establishment in a legacy city - Erika R. Wright; Christopher B. Riley; Ellen Danford; Samuel F. Ward; Mary M. Gardiner (Urban Forestry & Urban Greening, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Distributed optical fibre sensing in physical oceanography: emergence and future prospects - Alberto C. Naveira Garabato; Carl P. Spingys; Andrew J. Lucas; Tiago S. Dotto; Christian T. Wild; Scott W. Tyler; Ted A. Scambos; Christopher B. Kratt; Giuseppe Cappelli; Ethan F. Williams; Mariona Claret; Hannah E. Glover; et al. (Ocean Science, 2026)
Distributed optical fibre sensing (DOFS) is a technology that enables continuous, real-time measurements of a range of environmental parameters along the length of a fibre optic cable. In this article, we review the recently emerged applications of DOFS techniques in physical oceanography and offer a perspective on the technology's potential for future growth within the field. The introduction of DOFS to physical oceanography is contextualised with a brief history of the technology, which spun off primarily from the use of seafloor-laid optical fibres for telecommunications purposes. The key components and underpinning physics of a DOFS system are outlined and, on their basis, the suite of variables that are observable with DOFS are discussed. The implementation factors of DOFS, which include trade-offs between measurement accuracy and spatio-temporal resolutions and ranges, are also examined. The physical oceanographic applications of DOFS to date are then illustrated with case examples of four distinct DOFS techniques: distributed temperature sensing (DTS), which can provide ocean temperature observations; distributed static strain sensing (DSS) and distributed acoustic sensing (DAS), which are sensitive to temperature, cable strain and strain-associated variables, such as pressure and ocean velocity; and ultra-long-range observations of ocean currents with optical interferometry. The forthcoming prospects of DOFS in physical oceanography are considered, and are proposed to include new fibre optic-based approaches to sense ocean salinity and measure through the water column. We conclude with reflections on the future role of DOFS within the Global Ocean Observing System, and highlight the opportunities provided by the existing world-wide network of seafloor-laid optical fibres.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The interactive effects of nitrate and road salt on benthic algal assemblages in an artificial stream experiment - Margaret R. Menso; Christopher S. Ward; Paul A. Moore (Hydrobiologia, 2026)
Urban surface water runoff contains high levels of salt and nitrate, particularly in northern climates of the USA. We hypothesized that increased salt and nitrate concentrations would reduce total biomass and cause complete taxonomic shifts of benthic algae. To investigate and quantify the multi-tiered responses of benthic algal assemblages to the impacts of road salt and nitrate, we created artificial flow-through streams with terracotta vessels with nutrient diffusing substrates (NDS) containing varying concentrations of both salt (0–7500 mg/L) and nitrate (0–5.9 mg/L) and incubated for 56 days during the summer. Diatom concentrations were significantly impacted by salt, and the combination of salt and nitrate on sampling days 4 and 28. Over the range of tested nitrate conditions, some cyanobacteria increased over time. Within the eukaryotic community, several algal family abundances changed significantly over time. The response of diatoms was complex, with treatment only significantly impacting specific genera. Overall, this study shows salt and nitrate, as well as the combined effects of the two, significantly impact benthic algae assemblages and community development.

Projecting stream water quality using Weighted Regression on Time, Discharge, and Season (WRTDS): An example with drought conditions in the Delaware River Basin - Christopher T. Green; Robert M. Hirsch; Hedeff I. Essaid; Ward E. Sanford (Science of The Total Environment, 2025)

Environmental and Geographic Conditions on the Breeding Grounds Drive Bergmannian Clines in Nightjars - Aaron A. Skinner; Alicia M. Korpach; Susanne Åkesson; Marja H. Bakermans; Erin M. Bayne; Thomas J. Benson; Giovanni Boano; R. Mark Brigham; Simon S. Christiansen; Greg J. Conway; Christina M. Davy; Ruben Evens; et al. (Journal of Biogeography, 2025)
Aim To evaluate (1) whether three migratory nightjar species (Family Caprimulgidae) adhere to Bergmann's rule, (2) whether environmental factors on the breeding or wintering grounds determine body size, and (3) which mechanistic hypotheses best explain Bergmannian patterns in body size. Location North and South America; Europe and Africa. Taxon Eastern whip‐poor‐will ( Antrostomus vociferus ), Common nighthawk ( Chordeiles minor ) and European nightjar ( Caprimulgus europaeus ). Methods We used GPS tracking and morphometric data to assess competing hypotheses explaining variation in body size for each species, based on their breeding ( n = 3388) and wintering ( n = 189) locations. Results All three species exhibited Bergmannian patterns in body size, providing the first evidence that nightjars conform to Bergmann's rule despite adaptations to severe environmental conditions. Environmental and geographic variables at breeding sites were stronger predictors of body size than wintering‐site variables. Although we found partial support for Bergmann's temperature regulation hypothesis, geographic variables, rather than specific environmental factors, emerged as the strongest predictors of body size variation. Main Conclusions Latitude and longitude correlated strongly with environmental variables and migratory distance; thus, these geographical variables likely encompass many factors that influence body size in nightjars. The present study is among the first to use tracking data from individual birds to understand how environmental pressures across the annual cycle are related to body size. Our findings highlight the critical role of geographic breeding‐ground factors in shaping Bergmannian patterns, offering robust evidence to support nearly two centuries of research since Bergmann's rule was first described in 1847.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Remembering Don Bryant (1950–2024) - Christopher J. Gisriel; Wendy M. Schluchter; Fei Gan; John H. Golbeck; Ming-Yang Ho; Gaozhong Shen; Nathan T. Soulier; Vera Thiel; David M. Ward; Jindong Zhao; Shuyi Zhang (Photosynthesis Research, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Metabolism diversification of ammonia-oxidizing archaea and bacteria under different precipitation gradients and land legacies - Soumyadev Sarkar; Anna Kazarina; Paige M. Hansen; Kaitlyn Ward; Christopher Hargreaves; Nicholas Reese; Qinghong Ran; Willow Kessler; Ligia F.T. de Souza; Terry D. Loecke; Marcos V.M. Sarto; Charles W. Rice; et al. (Applied Soil Ecology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Coefficients in Taylor's law increase with the time scale of water clarity measurements in a global suite of lakes - Max R. Glines; Renata C. H. Amancio; Mikkel René Andersen; Helen Baulch; Ludmila S. Brighenti; Hannah E. Chmiel; Joel E. Cohen; Elvira de Eyto; Oxana Erina; Heidrun Feuchtmayr; Giovanna Flaim; Andrea Giudici; et al. (Ecology Letters, 2024)
Identifying the scaling rules describing ecological patterns across time and space is a central challenge in ecology. Taylor's law of fluctuation scaling, which states that the variance of a population's size or density is proportional to a positive power of the mean size or density, has been widely observed in population dynamics and characterizes variability in multiple scientific domains. However, it is unclear if this phenomenon accurately describes ecological patterns across many orders of magnitude in time, and therefore links otherwise disparate observations. Here, we use water clarity observations from 10,531 days of high‐frequency measurements in 35 globally distributed lakes, and lower‐frequency measurements over multiple decades from 6342 lakes to test this unknown. We focus on water clarity as an integrative ecological characteristic that responds to both biotic and abiotic drivers. We provide the first documentation that variations in ecological measurements across diverse sites and temporal scales exhibit variance patterns consistent with Taylor's law, and that model coefficients increase in a predictable yet non‐linear manner with decreasing observation frequency. This discovery effectively links high‐frequency sensor network observations with long‐term historical monitoring records, thereby affording new opportunities to understand and predict ecological dynamics on time scales from days to decades.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Smart Choices Start Here: Engaging Small Food Retailers and Consumers Through Shop Smart Tennessee - Christopher Sneed; Cori Sweet; Betsy Anderson-Steeves; Karen Franck; Jeanmarie Salie; Jennifer Ward; Kristen Johnson (Journal of Nutrition Education and Behavior, 2024)

The recent disappearance of a persistent Planktothrix bloom: Characterization of a regime shift in the phytoplankton of Sandusky Bay (USA) - Ryan S. Wagner; Michelle J. Neudeck; Alexis E. Heath; Katelyn B. Barker; Katelyn M. Brown; Seth Buchholz; Christopher S. Ward; George S. Bullerjahn (Harmful Algae, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Reclassifying historical disasters: From single to multi-hazards - Ryan Lee; Christopher J. White; Mohammed Sarfaraz Gani Adnan; John Douglas; Miguel D. Mahecha; Fiachra E. O'Loughlin; Edoardo Patelli; Alexandre M. Ramos; Matthew J. Roberts; Olivia Martius; Enrico Tubaldi; Bart van den Hurk; et al. (Science of The Total Environment, 2024)

Coprolites of the ichnogenus Alococopros from the Late Cretaceous of Morocco - Christopher J. Duffin; David J. Ward (Proceedings of the Geologists' Association, 2024)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Coherence among Oregon Coast coho salmon populations highlights increasing relative importance of marine conditions for productivity - Melanie J. Davis; James Anthony; Eric J. Ward; Julie Firman; Christopher Lorion (Fisheries Oceanography, 2023)
Anadromous fishes, such as Pacific salmon, spend portions of their life cycle in freshwater and marine systems, thus rendering them susceptible to a variety of natural and anthropogenic stressors. These stressors operate at different spatiotemporal scales, whereby freshwater conditions are more likely to impact single populations or subpopulations, while marine conditions are more likely to act on entire evolutionarily significant units (ESUs). Coherence in population parameters like survival and productivity can therefore serve as an indicator of relative influence. The goal of this study was to elucidate scale‐dependent shifts in Oregon Coast coho salmon productivity. We used a multivariate state‐space approach to analyze almost 60 years of stock‐recruitment data for the Oregon Coast ESU. Analyses were conducted separately for time periods prior to and after 1990 to account for improvements in abundance estimation methods and significant changes in conservation and management strategies. Prior to 1990, productivity declined for most Oregon Coast populations, especially through the 1980s. From 1990–onward, coherence increased, and trends tracked closely with the North Pacific Gyre Oscillation (NPGO). The latter period is associated with reductions in harvest rates and hatchery production such that the relative influence of the marine environment may have grown more apparent following the removal of these stressors. Furthermore, the link between productivity and NPGO is consistent with trends observed for several other Pacific salmon ESUs. If Oregon Coast coho salmon populations become more synchronous, managers can expect to face new challenges driven by reductions in the population portfolio effect and increasingly variable marine conditions due to climate change.

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Residual correlation and ensemble modelling to improve crop and grassland models - Renáta Sándor; Fiona Ehrhardt; Peter Grace; Sylvie Recous; Pete Smith; Val Snow; Jean-François Soussana; Bruno Basso; Arti Bhatia; Lorenzo Brilli; Jordi Doltra; Christopher D. Dorich; et al. (Environmental Modelling & Software, 2023)

Reaching Food Retail Customers Through Facebook - Cori Sweet; Jennifer Ward; Jeanmarie Salie; Karen Franck; Elizabeth Anderson Steeves; Christopher T. Sneed; Janie Burney (Journal of Nutrition Education and Behavior, 2023)

Recommendations for quantifying and reducing uncertainty in climate projections of species distributions - Stephanie Brodie; James A. Smith; Barbara A. Muhling; Lewis A. K. Barnett; Gemma Carroll; Paul Fiedler; Steven J. Bograd; Elliott L. Hazen; Michael G. Jacox; Kelly S. Andrews; Cheryl L. Barnes; Lisa G. Crozier; et al. (Global Change Biology, 2022)
Projecting the future distributions of commercially and ecologically important species has become a critical approach for ecosystem managers to strategically anticipate change, but large uncertainties in projections limit climate adaptation planning. Although distribution projections are primarily used to understand the scope of potential change—rather than accurately predict specific outcomes—it is nonetheless essential to understand where and why projections can give implausible results and to identify which processes contribute to uncertainty. Here, we use a series of simulated species distributions, an ensemble of 252 species distribution models, and an ensemble of three regional ocean climate projections, to isolate the influences of uncertainty from earth system model spread and from ecological modeling. The simulations encompass marine species with different functional traits and ecological preferences to more broadly address resource manager and fishery stakeholder needs, and provide a simulated true state with which to evaluate projections. We present our results relative to the degree of environmental extrapolation from historical conditions, which helps facilitate interpretation by ecological modelers working in diverse systems. We found uncertainty associated with species distribution models can exceed uncertainty generated from diverging earth system models (up to 70% of total uncertainty by 2100), and that this result was consistent across species traits. Species distribution model uncertainty increased through time and was primarily related to the degree to which models extrapolated into novel environmental conditions but moderated by how well models captured the underlying dynamics driving species distributions. The predictive power of simulated species distribution models remained relatively high in the first 30 years of projections, in alignment with the time period in which stakeholders make strategic decisions based on climate information. By understanding sources of uncertainty, and how they change at different forecast horizons, we provide recommendations for projecting species distribution models under global climate change.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Rapid changes in coastal ocean microbiomes uncoupled with shifts in environmental variables - Jessica L. Gronniger; Zhao Wang; Genevieve R. Brandt; Christopher S. Ward; Despina Tsementzi; Han Mu; Junyao Gu; Zackary I. Johnson; Konstantinos T. Konstantinidis; Dana E. Hunt (Environmental Microbiology, 2022)
Summary Disturbances, here defined as events that directly alter microbial community composition, are commonly studied in host‐associated and engineered systems. In spite of global change both altering environmental averages and increasing extreme events, there has been relatively little research into the causes, persistence and population‐level impacts of disturbance in the dynamic coastal ocean. Here, we utilize 3 years of observations from a coastal time series to identify disturbances based on the largest week‐over‐week changes in the microbiome (i.e. identifying disturbance as events that alter the community composition). In general, these microbiome disturbances were not clearly linked to specific environmental factors and responsive taxa largely differed, aside from SAR11, which generally declined. However, several disturbance metagenomes identified increased phage‐associated genes, suggesting that unexplained community shifts might be caused by increased mortality. Furthermore, a category 1 hurricane, the only event that would likely be classified a priori as an environmental disturbance, was not an outlier in microbiome composition, but did enhance a bloom in seasonally abundant phytoplankton. Thus, as extreme environmental changes intensify, assumptions of what constitutes a disturbance should be re‐examined in the context of ecological history and microbiome responses.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Oceans and society: feedbacks between ocean and human health - Kirsty L. Nash; Ingrid van Putten; Karen A. Alexander; Silvana Bettiol; Christopher Cvitanovic; Anna K. Farmery; Emily J. Flies; Sierra Ison; Rachel Kelly; Mary Mackay; Linda Murray; Kimberley Norris; et al. (Reviews in Fish Biology and Fisheries, 2022)

Embryonic antipredator defenses and behavioral carryover effects in the fathead minnow (Pimephales promelas) - Christopher Crowder; Jessica Ward (Behavioral Ecology and Sociobiology, 2022)

Microbiome Development of Seawater-Incubated Pre-production Plastic Pellets Reveals Distinct and Predictive Community Compositions - Christopher S. Ward; Zoie Diana; Kate Meicong Ke; Beatriz Orihuela; Thomas P. Schultz; Daniel Rittschof (Frontiers in Marine Science, 2022)
Plastics of various chemistries pollute global water bodies. Toxic chemicals leach with detrimental and often unpredictable impacts on the surrounding ecosystems. We found that seawater leachates of plastic pre-production pellets from 7 recycle categories are acutely toxic to stage II barnacle nauplii; lethal concentration 50 (LC50s) were observed in 24-h leachates from dilutions ranging from 0.007 to 2.1 mg/mL of seawater. Based on previous observations that macro-organismal settlement on fouling management coatings of various toxicities can be used to predict the toxicity of the coating, we hypothesized that interaction of plastic pre-production pellets with emerging microbiomes would exhibit patterns indicative of the chemistry at the pellet surface. We used amplicon sequencing of bacterial 16S ribosomal RNA genes to characterize the microbiomes that developed from 8 through 70 days on pellets exposed to the same flowing ambient seawater. Diversity and composition of the microbiomes colonizing plastic pellets changed over time and varied with plastic type. Microbial taxa belong to taxonomic groups known to consume hydrocarbons, to be prevalent following marine oil spills, or to live on fouling management surfaces. Microbiomes were still distinct between plastic types at Day 70, suggesting that differences in the physicochemical characteristics of the underlying plastics continue to exert variable selection of surface microbial communities. A random forest-based sample classifier correctly predicted 93% of plastic types using microbiome compositions. Surface microbiomes have promise for use in forensically identifying plastic types and potential toxicities.

Contrasting climate velocity impacts in warm and cool locations show that effects of marine warming are worse in already warmer temperate waters - Philina A. English; Eric J. Ward; Christopher N. Rooper; Robyn E. Forrest; Luke A. Rogers; Karen L. Hunter; Andrew M. Edwards; Brendan M. Connors; Sean C. Anderson (Fish and Fisheries, 2022)
Species responses to climate change are often measured at broad spatiotemporal scales, which can miss the fine‐scale changes that are most relevant to conservation and fisheries management. We develop a scaleable geostatistical approach to assess how juvenile and adult fish distributions have been shaped by changes in bottom temperature and dissolved oxygen over a recent decade of warming in the northeast Pacific. Across 38 demersal fishes, biomass trends were associated negatively with warming and positively with dissolved oxygen, but when trends in both biomass and climate were converted to velocities—the speed and direction a population would have to move to maintain consistent conditions—the effect of temperature change differed depending on local conditions. In the warmest locations, warming velocities were associated with negative biotic velocities for 19 of 69 species‐maturity combinations, and yet were almost always associated with stable or positive biotic velocities in the coolest locations (64 of 69). These spatially consistent biomass declines (negative biotic velocities) in the warmest locations and increases in cooler locations suggest a redistribution of species with the potential for new ecological and fisheries interactions. After controlling for temperature, the more spatially consistent effects of dissolved oxygen were often negative, suggesting a mechanism other than hypoxia avoidance—potentially changes in primary production. Our approach identifies the species and locations that are most sensitive to observed changes in the environment at any scale, thus facilitating future vulnerability assessments.

Grounding global environmental assessments through bottom-up futures based on local practices and perspectives - Laura Pereira; Ghassem R. Asrar; Rohan Bhargava; Laur Hesse Fisher; Angel Hsu; Jason Jabbour; Jeanne Nel; Odirilwe Selomane; Nadia Sitas; Christopher Trisos; James Ward; Mandy van den Ende; et al. (Sustainability Science, 2021)
Future scenarios and pathways of potential development trajectories are powerful tools to assist with decision-making to address many sustainability challenges. Such scenarios play a major role in global environmental assessments (GEAs). Currently, however, scenarios in GEAs are mostly developed at the global level by experts and researchers, and locally imagined, bottom-up scenarios do not play a role in such assessments. In this paper, we argue that addressing future sustainability challenges for achieving more equitable development in GEAs requires a more explicit role for bottom-up inspired futures. To this end, this paper employs an innovative global assessment framework for exploring alternative futures that are grounded in local realities and existing practical actions, and that can be appropriately scaled to the required decision-making level. This framework was applied in the context of the UN’s Global Environment Outlook 6, a major example of a GEA. We developed novel methods for synthesizing insights from a wide range of local practices and perspectives into global futures. We collected information from crowdsourcing platforms, outcomes of participatory workshops in different regions of the world, and an assessment of reported regional outlooks. We analysed these according to a framework also used by an integrated assessment model in the same GEA. We conclude that bottom-up approaches to identify and assess transformative solutions that envision future pathways towards greater sustainability significantly strengthen current GEA scenario-development approaches. They provide decision makers with required actionable information based on tangible synergistic solutions that have been tested on the ground. This work has revealed that there are significant opportunities for the integration of bottom-up knowledge and insights into GEAs, to make such assessments more salient and valuable to decision makers.

Dysfunctional sleep insufficiency and reduced P3 attentional response to positive social information - Steven L. Bistricky; Christine Walther; Jessica Balderas; Jasmin Prudon; Christopher P. Ward; Rick E. Ingram; Ruth Ann Atchley (Sleep and Biological Rhythms, 2021)

Disruption of duplicated yellow genes in Bactrocera tryoni modifies pigmentation colouration and impacts behaviour - Thu N. M. Nguyen; Vivian Mendez; Christopher Ward; Peter Crisp; Alexie Papanicolaou; Amanda Choo; Phillip W. Taylor; Simon W. Baxter (Journal of Pest Science, 2021)

Compositional and Functional Microbiome Variation Between Tubes of an Intertidal Polychaete and Surrounding Marine Sediment - Matthew Fuirst; Christopher S. Ward; Caroline Schwaner; Zoie Diana; Thomas F. Schultz; Daniel Rittschof (Frontiers in Marine Science, 2021)
The decorator worm Diopatra cuprea , a tube-forming marine polychaete common to intertidal and shallow subtidal waters, modifies habitats it occupies through microreef construction and algal gardening. While several studies have demonstrated that decorator worm tubes are hotspots of biogeochemical activity (i.e., nitrogen and sulfur cycling), it is still largely unclear whether the tube microbiome differs compositionally from the surrounding sediment and what distinct functional processes tube microbiomes may have. To address these unknowns, this study analyzed the bacterial communities of D. cuprea tubes and surrounding sediments using high-throughput 16S rRNA gene amplicon sequencing. Tubes and sediments were sampled at three sites along an anthropogenic stress gradient within the Newport River Estuary to also assess geographic variation of tube microbiomes and the possible influence of human disturbance. We found a clear distinction in the microbial community composition and diversity between tubes and surrounding sediment. Tube microbiomes were significantly enriched for the phyla Bacteriodetes, Actinobacteria, Verrucomicrobia, Deferribacteres, Latescibacteria, and Lentisphaerae. Chloroplast sequences of macroalgae and grass species were consistently abundant in tubes and nearly absent in surrounding sediment. Functional annotation of prokaryotic taxa (FAPROTAX)-based functional predictions suggested that tube microbiomes have higher potentials for aerobic chemoheterotrophy, sulfur compound respiration, nitrate reduction, methylotrophy, and hydrocarbon degradation than surrounding sediments. Tube microbiomes vary across sites, though dissimilarity is comparatively low compared to tube-to-sediment differences. Contrary to our hypothesis, the tubes at the most highly impacted site had the highest microbial diversity [i.e., amplicon sequence variant (ASV) richness and Shannon’s diversity], yet tubes from the medium impacted site actually had the lowest microbial diversity. Our findings show that D. cuprea tubes support a microbiome that is significantly distinct in composition and function from the surrounding sediment. Diopatra cuprea tubes appear to create unique microhabitats that facilitate numerous microbially-mediated biogeochemical processes in the marine benthic environment.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Synoptic timescale linkage between midlatitude winter troughs Sahara temperature patterns and northern Congo rainfall: A building block of regional climate variability - Neil Ward; Andreas H. Fink; Richard J. Keane; Françoise Guichard; John H. Marsham; Douglas J. Parker; Christopher M. Taylor (International Journal of Climatology, 2021)
A coherent synoptic sequence, mostly over North Africa, is identified whereby an upper‐level midlatitude trough (in November–March) excites several days of quasi‐stationary near‐surface warming across the Sahara, leading to rainfall events over northern Congo (NC), and perturbed weather more widely. Ahead of NC rainfall events, composite sequences first identify troughs for several days near Iberia, followed by relatively quick transfer to the Central Mediterranean (CMed). Iberia and CMed daily trough‐strength indices reveal that both lead to warming and NC rainfall. Iberia trough linkages develop through West Africa and take longer to reach NC, while CMed linkages reach NC faster (2–3 days), with impact extent focused mostly south and east of CMed. Building up to the rainfall events, initial warming over the central Sahara migrates southeastward close to NC, ultimately with typical magnitude of about 1–2°C at 10–15°N. Such anomalies are statistically predictive for NC daily rainfall and associated nearby atmospheric features: anomalous low‐level southerly wind and increased moisture; anomalous low‐level westerly wind and vertical easterly shear to 600 hPa; increased mid‐level moisture (600 hPa), which along with low‐level moisture, connects northward into midlatitudes. A secondary route identified by which Iberia troughs can impact NC rainfall is through direct atmospheric teleconnection with precipitation to the west of NC, and subsequent migration of that convection eastward into NC. The eastern side of NC generally shows a small lag on western parts, and links more strongly to CMed troughs. Taken together, the lagged synoptic expression of Iberia and CMed troughs is widespread over several days, including much of North Africa (to equatorial latitudes), southwestern Asia, eastern Africa and the western Indian Ocean. Overall, these results can contribute to situational awareness for weather forecasters across the zones influenced by the troughs, while also providing a framework for climate timescale analyses.

Ensemble modelling, uncertainty and robust predictions of organic carbon in long‐term bare‐fallow soils - Roberta Farina; Renata Sándor; Mohamed Abdalla; Jorge Álvaro‐Fuentes; Luca Bechini; Martin A. Bolinder; Lorenzo Brilli; Claire Chenu; Hugues Clivot; Massimiliano De Antoni Migliorati; Claudia Di Bene; Christopher D. Dorich; et al. (Global Change Biology, 2021)
Simulation models represent soil organic carbon (SOC) dynamics in global carbon (C) cycle scenarios to support climate‐change studies. It is imperative to increase confidence in long‐term predictions of SOC dynamics by reducing the uncertainty in model estimates. We evaluated SOC simulated from an ensemble of 26 process‐based C models by comparing simulations to experimental data from seven long‐term bare‐fallow (vegetation‐free) plots at six sites: Denmark (two sites), France, Russia, Sweden and the United Kingdom. The decay of SOC in these plots has been monitored for decades since the last inputs of plant material, providing the opportunity to test decomposition without the continuous input of new organic material. The models were run independently over multi‐year simulation periods (from 28 to 80 years) in a blind test with no calibration (Bln) and with the following three calibration scenarios, each providing different levels of information and/or allowing different levels of model fitting: (a) calibrating decomposition parameters separately at each experimental site (Spe); (b) using a generic, knowledge‐based, parameterization applicable in the Central European region (Gen); and (c) using a combination of both (a) and (b) strategies (Mix). We addressed uncertainties from different modelling approaches with or without spin‐up initialization of SOC. Changes in the multi‐model median (MMM) of SOC were used as descriptors of the ensemble performance. On average across sites, Gen proved adequate in describing changes in SOC, with MMM equal to average SOC (and standard deviation) of 39.2 (±15.5) Mg C/ha compared to the observed mean of 36.0 (±19.7) Mg C/ha (last observed year), indicating sufficiently reliable SOC estimates. Moving to Mix (37.5 ± 16.7 Mg C/ha) and Spe (36.8 ± 19.8 Mg C/ha) provided only marginal gains in accuracy, but modellers would need to apply more knowledge and a greater calibration effort than in Gen, thereby limiting the wider applicability of models.

Experimental metatranscriptomics reveals the costs and benefits of dissolved organic matter photo‐alteration for freshwater microbes - Sarah G. Nalven; Collin P. Ward; Jérôme P. Payet; Rose M. Cory; George W. Kling; Thomas J. Sharpton; Christopher M. Sullivan; Byron C. Crump (Environmental Microbiology, 2020)
Summary Microbes and sunlight convert terrigenous dissolved organic matter (DOM) in surface waters to greenhouse gases. Prior studies show contrasting results about how biological and photochemical processes interact to contribute to the degradation of DOM. In this study, DOM leached from the organic layer of tundra soil was exposed to natural sunlight or kept in the dark, incubated in the dark with the natural microbial community, and analysed for gene expression and DOM chemical composition. Microbial gene expression (metatranscriptomics) in light and dark treatments diverged substantially after 4 h. Gene expression suggested that sunlight exposure of DOM initially stimulated microbial growth by (i) replacing the function of enzymes that degrade higher molecular weight DOM such as enzymes for aromatic carbon degradation, oxygenation, and decarboxylation, and (ii) releasing low molecular weight compounds and inorganic nutrients from DOM. However, growth stimulation following sunlight exposure of DOM came at a cost. Sunlight depleted the pool of aromatic compounds that supported microbial growth in the dark treatment, ultimately causing slower growth in the light treatment over 5 days. These first measurements of microbial metatranscriptomic responses to photo‐alteration of DOM provide a mechanistic explanation for how sunlight exposure of terrigenous DOM alters microbial processing and respiration of DOM.

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Regional entropy of functional imaging signals varies differently in sensory and cognitive systems during propofol-modulated loss and return of behavioral responsiveness - Xiaolin Liu; Kathryn K. Lauer; B. Douglas Ward; Christopher J. Roberts; Suyan Liu; Suneeta Gollapudy; Robert Rohloff; William Gross; Zhan Xu; Shanshan Chen; Lubin Wang; Zheng Yang; et al. (Brain Imaging and Behavior, 2019)

Evapotranspiration and water yield of a pine‐broadleaf forest are not altered by long‐term atmospheric [CO 2 ] enrichment under native or enhanced soil fertility - Eric J. Ward; Ram Oren; Hyun Seok Kim; Dohyoung Kim; Pantana Tor‐ngern; Brent E. Ewers; Heather R. McCarthy; Andrew Christopher Oishi; Diane E. Pataki; Sari Palmroth; Nathan G. Phillips; Karina V. R. Schäfer (Global Change Biology, 2018)
Changes in evapotranspiration ( ET ) from terrestrial ecosystems affect their water yield ( WY ), with considerable ecological and economic consequences. Increases in surface runoff observed over the past century have been attributed to increasing atmospheric CO 2 concentrations resulting in reduced ET by terrestrial ecosystems. Here, we evaluate the water balance of a Pinus taeda (L.) forest with a broadleaf component that was exposed to atmospheric [CO 2 ] enrichment (ECO 2 ; +200 ppm) for over 17 years and fertilization for 6 years, monitored with hundreds of environmental and sap flux sensors on a half‐hourly basis. These measurements were synthesized using a one‐dimensional Richard's equation model to evaluate treatment differences in transpiration ( T ), evaporation ( E ), ET , and WY . We found that ECO 2 did not create significant differences in stand T, ET , or WY under either native or enhanced soil fertility, despite a 20% and 13% increase in leaf area index, respectively. While T , ET , and WY responded to fertilization, this response was weak ( E responded to ECO 2 in the first 7 years of the study, this effect was of negligible magnitude ( P. taeda , our results imply that recent observations of increased global streamflow cannot be attributed to decreases in ET across all ecosystems, demonstrating a great need for model–data synthesis activities to incorporate our current understanding of terrestrial vegetation in global water cycle models.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Advancing Marine Biological Observations and Data Requirements of the Complementary Essential Ocean Variables (EOVs) and Essential Biodiversity Variables (EBVs) Frameworks - Frank E. Muller-Karger; Patricia Miloslavich; Nicholas J. Bax; Samantha Simmons; Mark J. Costello; Isabel Sousa Pinto; Gabrielle Canonico; Woody Turner; Michael Gill; Enrique Montes; Benjamin D. Best; Jay Pearlman; et al. (Frontiers in Marine Science, 2018)

Blue-Green Water Nexus in Aquaculture for Resilience to Climate Change - Nesar Ahmed; James D. Ward; Shirley Thompson; Christopher P. Saint; James S. Diana (Reviews in Fisheries Science & Aquaculture, 2018)

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Range position and climate sensitivity: The structure of among‐population demographic responses to climatic variation - Staci M. Amburgey; David A. W. Miller; Evan H. Campbell Grant; Tracy A. G. Rittenhouse; Michael F. Benard; Jonathan L. Richardson; Mark C. Urban; Ward Hughson; Adrianne B. Brand; Christopher J. Davis; Carmen R. Hardin; Peter W. C. Paton; et al. (Global Change Biology, 2018)
Species’ distributions will respond to climate change based on the relationship between local demographic processes and climate and how this relationship varies based on range position. A rarely tested demographic prediction is that populations at the extremes of a species’ climate envelope (e.g., populations in areas with the highest mean annual temperature) will be most sensitive to local shifts in climate (i.e., warming). We tested this prediction using a dynamic species distribution model linking demographic rates to variation in temperature and precipitation for wood frogs ( Lithobates sylvaticus ) in North America. Using long‐term monitoring data from 746 populations in 27 study areas, we determined how climatic variation affected population growth rates and how these relationships varied with respect to long‐term climate. Some models supported the predicted pattern, with negative effects of extreme summer temperatures in hotter areas and positive effects on recruitment for summer water availability in drier areas. We also found evidence of interacting temperature and precipitation influencing population size, such as extreme heat having less of a negative effect in wetter areas. Other results were contrary to predictions, such as positive effects of summer water availability in wetter parts of the range and positive responses to winter warming especially in milder areas. In general, we found wood frogs were more sensitive to changes in temperature or temperature interacting with precipitation than to changes in precipitation alone. Our results suggest that sensitivity to changes in climate cannot be predicted simply by knowing locations within the species’ climate envelope. Many climate processes did not affect population growth rates in the predicted direction based on range position. Processes such as species‐interactions, local adaptation, and interactions with the physical landscape likely affect the responses we observed. Our work highlights the need to measure demographic responses to changing climate.

Hydrological Outlook UK: an operational streamflow and groundwater level forecasting system at monthly to seasonal time scales - Christel Prudhomme; Jamie Hannaford; Shaun Harrigan; David Boorman; Jeff Knight; Victoria Bell; Christopher Jackson; Cecilia Svensson; Simon Parry; Nuria Bachiller-Jareno; Helen Davies; Richard Davis; et al. (Hydrological Sciences Journal, 2017)

Gut microbiota-bone axis - Christopher R. Villa; Wendy E. Ward; Elena M. Comelli (Critical Reviews in Food Science and Nutrition, 2017)

Integrated approach to determining stock structure: implications for fisheries management of sardine, Sardinops sagax, in Australian waters - Christopher Izzo; Tim M. Ward; Alex R. Ivey; Iain M. Suthers; John Stewart; Stuart C. Sexton; Bronwyn M. Gillanders (Reviews in Fish Biology and Fisheries, 2017)

Dissolved Organic and Inorganic Carbon Flow Paths in an Amazonian Transitional Forest - Vania Neu; Nicholas D. Ward; Alex V. Krusche; Christopher Neill (Frontiers in Marine Science, 2016)

A Revised Brackish Water Aquifer Storage and Recovery (ASR) Site Selection Index for Water Resources Management - Christopher J. Brown; James Ward; June Mirecki (Water Resources Management, 2016)

The effect of multiple primary rules on cancer incidence rates and trends - Hannah K. Weir; Christopher J. Johnson; Kevin C. Ward; Michel P. Coleman (Cancer Causes & Control, 2016)

Thermally adaptive tradeoffs in closely related marine bacterial strains - Cheuk‐Man Yung; Marissa K. Vereen; Amy Herbert; Katherine M. Davis; Jiayu Yang; Agata Kantorowska; Christopher S. Ward; Jennifer J. Wernegreen; Zackary I. Johnson; Dana E. Hunt (Environmental Microbiology, 2015)
Summary Time series studies have shown that some bacterial taxa occur only at specific times of the year while others are ubiquitous in spite of seasonal shifts in environmental variables. Here, we ask if these ubiquitous clades are generalists that grow over a wide range of environmental conditions, or clusters of strain‐level environmental specialists. To answer this question, vibrio strains isolated at a coastal time series were phylogenetically and physiologically characterized revealing three dominant strategies within the vibrio: mesophiles, psychrophiles and apparently generalist broad thermal range clades. Thermal performance curves from laboratory growth rate experiments help explain field observations of relative abundances: the mesophilic clade grows optimally at temperatures 16°C higher than the psychrophilic clade. Strains in the broad thermal range clade all have similar optimal growth temperatures but also exhibit temperature‐related tradeoffs with faster growth rates for warm temperature strains and broader growth ranges for strains from cool temperatures. Moreover, the mechanisms of thermal adaptation apparently differ based on evolutionary time scales: shifts in the temperature of maximal growth occur between deeply branching clades but thermal performance curve shape changes on shorter time scales. Thus, apparently ubiquitous clades are likely not generalists, but contain subclusters with distinct environmental preferences.

On the difference in the net ecosystem exchange of CO 2 between deciduous and evergreen forests in the southeastern United States - Kimberly A. Novick; A. Christopher Oishi; Eric J. Ward; Mario B. S. Siqueira; Jehn‐Yih Juang; Paul C. Stoy (Global Change Biology, 2015)
The southeastern United States is experiencing a rapid regional increase in the ratio of pine to deciduous forest ecosystems at the same time it is experiencing changes in climate. This study is focused on exploring how these shifts will affect the carbon sink capacity of southeastern US forests, which we show here are among the strongest carbon sinks in the continental United States. Using eight‐year‐long eddy covariance records collected above a hardwood deciduous forest ( HW ) and a pine plantation ( PP ) co‐located in North Carolina, USA , we show that the net ecosystem exchange of CO 2 ( NEE ) was more variable in PP , contributing to variability in the difference in NEE between the two sites (Δ NEE ) at a range of timescales, including the interannual timescale. Because the variability in evapotranspiration ( ET ) was nearly identical across the two sites over a range of timescales, the factors that determined the variability in Δ NEE were dominated by those that tend to decouple NEE from ET . One such factor was water use efficiency, which changed dramatically in response to drought and also tended to increase monotonically in nondrought years ( P PP ). Factors that vary over seasonal timescales were strong determinants of the NEE in the HW site; however, seasonality was less important in the PP site, where significant amounts of carbon were assimilated outside of the active season, representing an important advantage of evergreen trees in warm, temperate climates. Additional variability in the fluxes at long‐time scales may be attributable to slowly evolving factors, including canopy structure and increases in dormant season air temperature. Taken together, study results suggest that the carbon sink in the southeastern United States may become more variable in the future, owing to a predicted increase in drought frequency and an increase in the fractional cover of southern pines.

Can integrated aquaculture-agriculture (IAA) produce “more crop per drop”? - Nesar Ahmed; James D. Ward; Christopher P. Saint (Food Security, 2014)

Transplantation of devitalized muscle scaffolds is insufficient for appreciable de novo muscle fiber regeneration after volumetric muscle loss injury - Koyal Garg; Catherine L. Ward; Christopher R. Rathbone; Benjamin T. Corona (Cell and Tissue Research, 2014)

Optimising diet decisions and urban agriculture using linear programming - James D. Ward; Peter J. Ward; Evangeline Mantzioris; Christopher Saint (Food Security, 2014)

Spatial variation in life‐history trade‐offs results in an ideal free distribution in Black Brant Geese - Christopher A. Nicolai; James S. Sedinger; David H. Ward; W. Sean Boyd (Ecology, 2014)
Ideal free distribution theory predicts that individuals distribute themselves so fitness is equal among patches. In this paper we evaluate all components of adult fitness to assess the hypothesis that individuals distribute themselves among seven brood‐rearing areas so that trade‐offs among different life history traits result in equal mean fitness among individuals using different areas. We used estimates of vital rates (clutch size, nest survival, pre‐fledging survival, post‐fledging survival, juvenile survival, and breeding probability) to estimate brood‐rearing‐area‐specific per capita recruitment rates and survival for adult females. We summed brood‐rearing‐area‐specific per capita recruitment and adult survival to calculate brood‐rearing‐area‐specific estimates of λ. We found little variation in λ among brood‐rearing areas and lifetime fitness implications of changing brood‐rearing area were negligible (

Contrasting Growth Patterns of Suspension-Feeding Molluscs (Mercenaria mercenaria, Crassostrea virginica, Argopecten irradians, and Crepidula fornicata) Across a Eutrophication Gradient in the Peconic Estuary, NY, USA - Charles C. Wall; Christopher J. Gobler; Bradley J. Peterson; J. Evan Ward (Estuaries and Coasts, 2013)

Performance of a Multi-disciplinary Emergency Department Observation Protocol for Acetaminophen Overdose - Gillian A. Beauchamp; Kimberly W. Hart; Christopher J. Lindsell; Michael S. Lyons; Edward J. Otten; Carol L. Smith; Michael J. Ward; Stewart W. Wright (Journal of Medical Toxicology, 2013)

Children's daily exposure to polychlorinated biphenyls from dietary supplements containing fish oils - Jeffrey T.F. Ashley; Joshua S. Ward; Christopher S. Anderson; Michael W. Schafer; Linda Zaoudeh; Richard J. Horwitz; David J. Velinsky (Food Additives & Contaminants: Part A, 2013)

Distribution of exotic monk parakeets across an urban landscape - Emily S. Minor; Christopher W. Appelt; Sean Grabiner; Lorrie Ward; Alexandra Moreno; Stephen Pruett-Jones (Urban Ecosystems, 2012)

Interactions among chronic and acute impacts on coral recruits: the importance of size‐escape thresholds - Christopher Doropoulos; Selina Ward; Alyssa Marshell; Guillermo Diaz-Pulido; Peter J. Mumby (Ecology, 2012)
Newly settled recruits typically suffer high mortality from disturbances, but rapid growth reduces their mortality once size‐escape thresholds are attained. Ocean acidification (OA) reduces the growth of recruiting benthic invertebrates, yet no direct effects on survivorship have been demonstrated. We tested whether the reduced growth of coral recruits caused by OA would increase their mortality by prolonging their vulnerability to an acute disturbance: fish herbivory on surrounding algal turf. After two months' growth in ambient or elevated CO 2 levels, the linear extension and calcification of coral ( Acropora millepora ) recruits decreased as CO 2 partial pressure ( p CO 2 ) increased. When recruits were subjected to incidental fish grazing, their mortality was inversely size dependent. However, we also found an additive effect of p CO 2 such that recruit mortality was higher under elevated p CO 2 irrespective of size. Compared to ambient conditions, coral recruits needed to double their size at the highest p CO 2 to escape incidental grazing mortality. This general trend was observed with three groups of predators (blenny, surgeonfish, and parrotfish), although the magnitude of the fish treatment varied among species. Our study demonstrates the importance of size‐escape thresholds in early recruit survival and how OA can shift these thresholds, potentially intensifying population bottlenecks in benthic invertebrate recruitment.

Ocean acidification reduces coral recruitment by disrupting intimate larval‐algal settlement interactions - Christopher Doropoulos; Selina Ward; Guillermo Diaz‐Pulido; Ove Hoegh‐Guldberg; Peter J. Mumby (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 338–346 Abstract Successful recruitment in shallow reef ecosystems often involves specific cues that connect planktonic invertebrate larvae with particular crustose coralline algae (CCA) during settlement. While ocean acidification (OA) can reduce larval settlement and the abundance of CCA, the impact of OA on the interactions between planktonic larvae and their preferred settlement substrate are unknown. Here, we demonstrate that CO 2 concentrations (800 and 1300 μatm) predicted to occur by the end of this century significantly reduce coral ( Acropora millepora ) settlement and CCA cover by ≥ 45%. The CCA important for inducing coral settlement ( Titanoderma spp., Hydrolithon spp.) were the most deleteriously affected by OA. Surprisingly, the only preferred settlement substrate ( Titanoderma ) in the experimental controls was avoided by coral larvae as p CO 2 increased, and other substrata selected. Our results suggest OA may reduce coral population recovery by reducing coral settlement rates, disrupting larval settlement behaviour, and reducing the availability of the most desirable coralline algal species for successful coral recruitment.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Germline PKHD1 mutations are protective against colorectal cancer - Christopher J. Ward; Yanhong Wu; Ruth A. Johnson; John R. Woollard; Eric J. Bergstralh; Mine S. Cicek; Jason Bakeberg; Sandro Rossetti; Christina M. Heyer; Gloria M. Petersen; Noralene M. Lindor; Stephen N. Thibodeau; et al. (Human Genetics, 2011)

Emergence of Complex Haplotypes from Microevolutionary Variation in Sequence and Structure of Colias Phosphoglucose Isomerase - Baiqing Wang; Ward B. Watt; Christopher Aakre; Noah Hawthorne (Journal of Molecular Evolution, 2009)

Sediment denitrifier community composition and nirS gene expression investigated with functional gene microarrays - Silvia E. Bulow; Christopher A. Francis; George A. Jackson; Bess B. Ward (Environmental Microbiology, 2008)
Summary A functional gene microarray was used to investigate denitrifier community composition and nitrite reductase ( nirS ) gene expression in sediments along the estuarine gradient in Chesapeake Bay, USA. The nirS oligonucleotide probe set was designed to represent a sequence database containing 539 Chesapeake Bay clones, as well as sequences from many other environments. Greatest nirS diversity was detected at the freshwater station at the head of the bay and least diversity at the higher salinity station near the mouth of the Bay. The most common OTUs from the sequence database were detected on the array with high signal strength in most samples. One of the most abundant OTUs, CB2‐S‐138, was identified as dominant at the mid‐bay site by both microarray and quantitative PCR assays, but it comprised a much smaller fraction of the assemblage in the north and south bay samples. cDNA (transcribed from total RNA extracts) targets were hybridized to the same array to compare the profiles of community composition at the DNA (relative abundance) and mRNA (gene expression) levels. Only the three dominant denitrifying groups (in terms of relative strength of DNA hybridization signal) were detected at the mRNA level. These results suggest that the most actively denitrifying groups are responsible for most nirS expression as well.

Sources for sedimentary bacteriohopanepolyols as revealed by 16S rDNA stratigraphy - Marco J. L. Coolen; Helen M. Talbot; Ben A. Abbas; Christopher Ward; Stefan Schouten; John K. Volkman; Jaap S. Sinninghe Damsté (Environmental Microbiology, 2008)
Summary Bacteriohopanoids are widespread lipid biomarkers in the sedimentary record. Many aerobic and anaerobic bacteria are potential sources of these lipids which sometimes complicates the use of these biomarkers as proxies for ecological and environmental changes. Therefore, we applied preserved 16S ribosomal RNA genes to identify likely Holocene biological sources of bacteriohopanepolyols (BHPs) in the sulfidic sediments of the permanently stratified postglacial Ace Lake, Antarctica. A suite of intact BHPs were identified, which revealed a variety of structural forms whose composition differed through the sediment core reflecting changes in bacterial populations induced by large changes in lake salinity. Stable isotopic compositions of the hopanols formed from periodic acid‐cleaved BHPs, showed that some were substantially depleted in 13 C, indicative of their methanotrophic origin. Using sensitive molecular tools, we found that Type I and II methanotrophic bacteria (respectively Methylomonas and Methylocystis ) were unique to the oldest lacustrine sediments (> 9400 years BP), but quantification of fossil DNA revealed that the Type I methanotrophs, including methanotrophs related to methanotrophic gill symbionts of deep‐sea cold‐seep mussels, were the main precursors of the 35‐amino BHPs (i.e. aminopentol, ‐tetrol and ‐triols). After isolation of the lake ∼3000 years ago, one Type I methanotroph of the ‘methanotrophic gill symbionts cluster’ remained the most obvious source of aminotetrol and ‐triol. We, furthermore, identified a Synechococcus phylotype related to pelagic freshwater strains in the oldest lacustrine sediments as a putative source of 2‐methylbacteriohopanetetrol (2‐Me BHT). This combined application of advanced geochemical and paleogenomical tools further refined our knowledge about Holocene biogeochemical processes in Ace Lake.

Discrete-trials heroin self-administration produces sensitization to the reinforcing effects of cocaine in rats - Sara J. Ward; Christopher Läck; Drake Morgan; David C. S. Roberts (Psychopharmacology, 2006)

NORTH ATLANTIC RIGHT WHALE DISTRIBUTION IN RELATION TO SEA‐SURFACE TEMPERATURE IN THE SOUTHEASTERN UNITED STATES CALVING GROUNDS - Chérie A. Keller; Leslie I. Ward‐Geiger; William B. Brooks; Christopher K. Slay; Cynthia R. Taylor; Barbara J. Zoodsma (Marine Mammal Science, 2006)
Standardized aerial surveys were used to document the winter (December–March) distribution of North Atlantic right whales in their calving area off the coasts of Georgia and northeastern Florida (1991–1998). Survey data were collected within four survey zones in and adjacent to federally designated critical habitat. These data, including whale‐sighting locations and sampling effort, were used to describe right whale distribution in relation to sea‐surface temperature (SST) from satellite‐derived images. Locations where whales were sighted ( n = 609) had an overall mean SST of 14.3°C ± 2.1° (range 8°–22°C). Data from two survey zones having sufficient data (including the “early warning system” (EWS) zone and the Florida nearshore) were pooled by season and stratified by month to investigate changes in monthly ambient SST and fine‐scale distribution patterns of right whales in relation to SST within spatially explicit search areas. Using Monte Carlo techniques, SSTs and latitudes (means and standard deviations) of locations where whales were sighted were compared to a sampling distribution of each variable derived from daily‐search areas. Overall, results support a nonrandom distribution of right whales in relation to SST: during resident months (January and February), whales exhibited low variability in observed SST and a suggested southward shift in whale distribution toward warmer SSTs in the EWS zone; while in the relatively warmer and southernmost survey zone (Florida nearshore), right whales were concentrated in the northern, cooler portion. Our results support that warm Gulf Stream waters, generally found south and east of delineated critical habitat, represent a thermal limit for right whales and play an important role in their distribution within the calving grounds. These results affirm the inclusion of SST in a multivariate predictive model for right whale distribution in their southeastern habitat.

Macroinvertebrate diversity in fragmented Alpine streams: implications for freshwater conservation - Michael T. Monaghan; Christopher T. Robinson; Piet Spaak; James V. Ward (Aquatic Sciences, 2005)

Macroinvertebrate diversity in fragmented Alpine streams: implications for freshwater conservation - Michael T. Monaghan; Christopher T. Robinson; Piet Spaak; James V. Ward (Aquatic Sciences, 2005)

The performance of models relating species geographical distributions to climate is independent of trophic level - Brian Huntley; Rhys E. Green; Yvonne C. Collingham; Jane K. Hill; Stephen G. Willis; Patrick J. Bartlein; Wolfgang Cramer; Ward J. M. Hagemeijer; Christopher J. Thomas (Ecology Letters, 2004)
Species–climate ‘envelope’ models are widely used to evaluate potential climate change impacts upon species and biodiversity. Previous studies have used a variety of methods to fit models making it difficult to assess relative model performance for different taxonomic groups, life forms or trophic levels. Here we use the same climatic data and modelling approach for 306 European species representing three major taxa (higher plants, insects and birds), and including species of different life form and from four trophic levels. Goodness‐of‐fit measures showed that useful models were fitted for >96% of species, and that model performance was related neither to major taxonomic group nor to trophic level. These results confirm that such climate envelope models provide the best approach currently available for evaluating reliably the potential impacts of future climate change upon biodiversity.

EXTRACELLULAR MATRIX INDUCES FORMATION OF ORGANOIDS AND CHANGES IN CELL SURFACE MORPHOLOGY IN CULTURED HUMAN BREAST CARCINOMA CELLS PMC42-LA - M. LEIGH ACKLAND; JOHN WARD; CHRISTOPHER M. ACKLAND; MARK GREAVES; MARY WALKER (In Vitro Cellular & Developmental Biology - Animal, 2003)

Extracellular matrix induces formation of organoids and changes in cell surface morphology in cultured human breast carcinoma cells PMC42-LA - Margaret Ackland; John Ward; Christopher Ackland; Mark Greaves; Mary Walker (In Vitro Cellular & Developmental Biology - Animal, 2003)

Biodegradation of dimethyl phthalate with high removal rates in a packed-bed reactor - Christopher Juneson; Owen P. Ward; Ajay Singh (World Journal of Microbiology and Biotechnology, 2002)

Tamoxifen inhibits Ca2+ uptake by the cardiac sarcoplasmic reticulum - Margaret E. Kargacin; Zenobia Ali; Christopher A. Ward; Natashka S. Pollock; Gary J. Kargacin (Pflügers Archiv - European Journal of Physiology, 2000)